Misdemeanours against public order in the Police Administration Split-Dalmatia - Damir Juras; Slobodan Marendić; Marko Doljanin (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The article defines misdemeanours against public order, provides statistical data on these misdemeanours in the Republic of Croatia, particularly within the jurisdiction of the Police Administration Split-Dalmatia. It also refers to relevant case law. Since the Police is responsible for processing these misdemeanours, the decisions on public order made by local government units in the County of Split-Dalmatia are analysed in detail. These decisions, in addition to those prescribed by the Law on Misdemeanours against Public Order, establish a normative framework for determining and sanctioning these offenses. The authors conclude that the legal framework for prosecuting misdemeanours against public order is sufficient, but it is necessary to remove provisions contained in laws, outdated provisions, and those that violate municipal regulations from sublegal acts. The local regulations on public order should regulate only specific unlawful actions that disrupt public order in particular (local) areas.